Sanksi Pidana pada Pencemaran Nama Baik dalam Melakukan Review Suatu Produk Usaha Tanpa Izin di Media Sosial - Laksitowati, Cahyorini; Ayu Ardhani Putri, Hanuring; Diyah Purnomo Wulan, Ida Aryati (LPPM Universitas Ekasakti Padang, 2024)
Development of technology today, the development and competition in the business field has also greatly increased. With the review column feature in the online application, business actors have many effective ways to promote products to be in demand by consumers in order to provide good reviews and reviews in the column provided by the application. In this regard, business actors need to pay attention to product reviews provided by consumers. Because the reviews given by consumers, both positive and negative, are very influential in the decision to buy products. However, many individuals are irresponsible in providing fake reviews that are not in accordance with reality that aim to bring down business actors. The purpose of this study is to analyze criminal sanctions for defamation actors in conducting business product reviews. This research uses a type of normative research, where normative legal research can be interpreted by doctrinal legal research and understanding the law to be a positive legal system in laws and regulations. The process of finding rules in law either regarding legal principles or doctrines that aim to answer legal issues. The results of the study frame that the activity of reviewing business products online is regulated in Article 27 Paragraph (3) of Law Number 19 of 2016 concerning amendments to Law Number 11 of 2008 concerning Electronic Information and Transactions, to aim to protect business actors in ecommerce in defamation.